Influence of exercise type and duration on cardiorespiratory fitness and muscular strength in post-menopausal women: a systematic review and meta-analysis - Khalafi, Mousa; Sakhaei, Mohammad Hossein; Habibi Maleki, Aref; Rosenkranz, Sara K.; Pourvaghar, Mohammad Javad; Fang, Yiqun; Korivi, Mallikarjuna (Frontiers in Cardiovascular Medicine, 2023)
Background and aim Both cardiorespiratory fitness (CRF) and muscular strength are reported to decrease with age and menopause, which considered to be risk for cardiovascular diseases (CVDs). Previous relevant meta-analyses are inconclusive on the beneficial effects of exercise, particularly in post-menopausal women. In this systematic review and meta-analysis, we investigated the effects of exercise modalities on CRF and muscular strength in post-menopausal women, and identified the effective exercise type and duration. Methods A comprehensive search was conducted on PubMed, Web of Science, CINAHL, and Medline to identify the randomized controlled trials, which evaluated exercise effect on CRF, lower- and upper-body muscular strength, and/or handgrip strength in post-menopausal women and compared the results with control. Standardized mean differences (SMD), weighted mean differences (WMD), and 95% confidence intervals (95% CIs) were calculated using random effects models. Results A total of 129 studies comprising 7,141 post-menopausal women with mean age and BMI ranging from ∼53 to 90 years and 22 to 35 kg/m2, respectively, were included in the meta-analysis. Overall, exercise training effectively increased CRF (SMD: 1.15; 95% CI: 0.87, 1.42; p = 0.001), lower-body muscular strength (SMD: 1.06; 95% CI: 0.90, 1.22; p = 0.001), upper-body muscular strength (SMD: 1.11; 95% CI: 0.91, 1.31; p = 0.001), and handgrip strength (WMD: 1.78 kg; 95% CI: 1.24, 2.32; p = 0.001) in post-menopausal women. These increments were found to be irrespective of ages and intervention durations. Regarding exercise type, aerobic, resistance, and combined training significantly increased CRF and lower-body muscular strength, while resistance and combined training effectively increased handgrip strength. However, only resistance training increased the upper-body muscular strength in women. Conclusion Our findings suggest that exercise training is effective in increasing CRF and muscular strength in post-menopausal women, which might be cardioprotective. Both aerobic and resistance training alone or in combination increased CRF and lower-body muscular strength, but only resistance training increased upper-body strength in women. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=283425, identifier: CRD42021283425.